Moderasi Promosi pada Pengaruh Perceived Ease of Use Terhadap Minat Penggunaan Paylater - Prajogo, Uke; Maulana, Moh. Zulfiqar Naufal (Universitas Merdeka Malang, 2023)
This research aims to analyze the influence of perceived ease of use on interest in using pay-later with the moderation of promotion. The research object is SMEs (small and Medium Enterprises) affiliated with ABM Preneur. The sampling method used is stratified purposive random sampling. The researcher determined the sample criteria as follows: 1. SMEs affiliated with ABM Preneur, 2. Awareness or prior use of Paylater. To determine the minimum sample size, the researcher used the Slovin Technique. The population size in this study is 71 SMEs, and a sample of 60 individuals was obtained. The sample size was determined using the Slovin formula. Data analysis was conducted using SmartPLS 3, where variable X1 is perceived ease of use, variable Y is interest in using pay-later, and variable Z is promotion. The research results show that H1 and H2 are accepted. Therefore, perceived ease of use has a positive and significant influence on interest in using pay-later. Promotion moderates the influence of perceived ease of use on interest in using pay-later. The limitation of this research is that it only analyzes the moderation of promotion and the influence of perceived ease of use on the interest in using pay-later in SMEs affiliated with ABM Preneur in Malang City.